HHV-6A Infection of Endometrial Epithelial Cells Induces Increased Endometrial NK Cell-Mediated Cytotoxicity - Caselli, Elisabetta; Bortolotti, Daria; Marci, Roberto; Rotola, Antonella; Gentili, Valentina; Soffritti, Irene; D’Accolti, Maria; Lo Monte, Giuseppe; Sicolo, Mariangela; Barao, Isabel; Di Luca, Dario; Rizzo, Roberta (Frontiers in Microbiology, 2017)
Background: We have recently reported the presence of Human herpesvirus-6A (HHV-6A) DNA in the 43% of endometrial epithelial cells from primary idiopathic infertile women, with no positivity in fertile women. To investigate the possible effect of HHV-6A infection in endometrial (e)NK cells functions, we examined activating/inhibitory receptors expressed by eNK cells and the corresponding ligands on endometrial cells during HHV-6A infection. Methods: Endometrial biopsies and uterine flushing samples during the secretory phase were obtained from 20 idiopathic infertile women and twenty fertile women. HHV-6A infection of endometrial epithelial cells was analyzed by Real-Time PCR, immunofluorescence and flow cytometry. eNKs receptors and endometrial ligands expression were evaluated by immunofluorescence and flow cytometry. Results: We observed the presence of HHV-6A infection (DNA, protein) of endometrial epithelial cells in the 40% of idiopathic infertile women. The eNK from all the subgroups expressed high levels of NKG2D and NKG2A receptors. Functional studies showed that NKG2D activating receptor and FasL are involved in the acquired cytotoxic function of eNK cells during HHV-6A infection of endometrial epithelial cells. In the presence of HHV-6A infection, eNK cells increased expression of CCR2, CXCR3 and CX3CR1 chemokine receptors (p = 0.01) and endometrial epithelial cells up-modulated the corresponding ligands: MCP1 (Monocyte chemotactic protein 1, CCL2), IP-10 (Interferon gamma-induced protein 10, CXCL10) and Eotaxin-3 (CCL26). Conclusion: Our results, for the first time, showed the implication of eNK cells in controlling HHV-6A endometrial infection and clarify the mechanisms that might be implicated in female idiopathic infertility.